PREVALENCE AND FACTORS ASSOCIATED WITH HYPERTENSION AMONG HEALTH WORKERS OF CENTRAL HOSPITALS IN NEPAL - Prakash Ghimire; Alisha Khadka; Amornrat Anuwatnonthakate; Supaporn Trongsakul (Universitas Airlangga, 2020)
Hypertension is a significant public health issue considered as the world's biggest killer among the working-age group. Health workers are one of the working groups who are facing several factors in their lives that could induce hypertension among them. Nevertheless, there is a lack of information about hypertension among Nepalese health workers. Therefore, this cross-sectional study aimed to determine the prevalence and factors associated with hypertension among health workers of central hospitals in Nepal. A total of 422 health workers aged ≥30 years from seven central hospitals of Nepal were selected using a proportionate stratified systematic random sampling method. Information regarding characteristics (socio-demographic, clinical, behavioral, occupational, and perceived stress) of participants were obtained by face to face interviews using a questionnaire after getting informed written consent. Participant's blood pressure and body mass index were measured based on the World Health Organization STEP Surveillance Manual. Binary logistic regression model was used to identify the associated factors of hypertension. The prevalence of hypertension was 35.31% (95% CI: 30.70%-40.10%). After controlling potential confounding factors through multivariate analysis, seven factors (increasing age, low educational level, being married, low fruit & vegetable consumption, low physical activity, alcohol use, and increased perceived stress) were found as significant independent predictors of hypertension. In conclusion, hypertension is highly prevalent among Nepalese health workers. Effective behavioral change interventions and routine health screening programs focusing on hypertension should be implemented to control hypertension among this neglected group, Nepalese health workers. Keywords: Health Workers, Hypertension, Perceived stress, Physical activity, Prevalence, Nepal